2021
DOI: 10.3390/v13091885
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic and Prognostic Biomarkers for Adenovirus Respiratory Infection in Children and Young Adults

Abstract: Human Adenoviruses (HAdV) are known to be potentially associated with strong inflammatory responses and morbidity in pediatric patients. Although most of the primary infections are self-limiting, the severity of clinical presentation, the elevation of the white blood cell count and inflammatory markers often mimic a bacterial infection and lead to an inappropriate use of antibiotics. In infections caused by HAdV, rapid antigen detection kits are advisable but not employed routinely; costs and feasibility of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 101 publications
(176 reference statements)
0
16
1
Order By: Relevance
“…The indicators of coagulation function, such as D-dimer and infection biomarkers such as PCT in severe patients, were significantly higher than those in mild patients. In previous studies, PCT was used as a sensitive indicator for detecting viral infections, and the level of PCT was correlated with the severity of viral infections to a certain extent [24,25]. This study indicates that the pathogenesis of severe adenovirus infection is related to the decrease of lymphocytes and the disorder of inflammatory response.…”
Section: Discussionmentioning
confidence: 54%
“…The indicators of coagulation function, such as D-dimer and infection biomarkers such as PCT in severe patients, were significantly higher than those in mild patients. In previous studies, PCT was used as a sensitive indicator for detecting viral infections, and the level of PCT was correlated with the severity of viral infections to a certain extent [24,25]. This study indicates that the pathogenesis of severe adenovirus infection is related to the decrease of lymphocytes and the disorder of inflammatory response.…”
Section: Discussionmentioning
confidence: 54%
“…The pathogenesis of severe disease induced by human AdV-7 may be related to high replication capacity and high inflammatory response [ 28 ]. AdV may be closely associated with a strong inflammatory response in pediatric patients [ 29 ]. Zhang et al showed that CRP and LDH levels were independent risk factors for BMP formation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary infection occurs during infancy and usually can be asymptomatic or simulate a self-limiting flu-like infection or intestinal gastroenteritis, while other severe manifestations, such as myocarditis, encephalitis, and meningitis, are rare [ 10 ].…”
Section: Biologymentioning
confidence: 99%